Outcomes and insights from a case series of laparoscopic gastrojejunostomy for gastric outlet obstruction - Verma, Sagar; Dadhich, Yogendra (International Surgery Journal, 2025)
Laparoscopic gastrojejunostomy (LGJ) has been proposed as the technique preferred over open gastrojejunostomy technique for relieving gastric outlet obstruction (GOO) due to malignant and benign disease. This study investigates the feasibility and safety of LGJ for GOO compared to the open technique of gastrojejunostomy. This retrospective study reviewed 10 patients (8 males, 2 females) who underwent LGJ at SMS Medical College and Hospital from 2023 to 2024. Data was collected from hospital records, focusing on patient demographics, medical history, symptoms, diagnostic workup, operative details, and postoperative outcomes. The long-term outcomes and survival rates were also assessed. The 10 patients had a mean age of 38.9 years (range: 30-74). Surgical indications included benign duodenal strictures (6 patients) along with 4 cases with malignancy (2 for palliative treatment of gallbladder carcinoma and 2 for pancreatic head carcinoma). The average operative time was 90 minutes, and the average hospital stay was 5 days. There were no intraoperative or postoperative mortalities, anastomotic leaks, conversions to open surgery, or dumping syndrome cases. Only one of the ten patients assessed, a case of pancreatic head carcinoma, experienced a complication in the form of grade A delayed gastric emptying. All other patients advanced to accept clear liquids by postoperative day 3 and semi-solid food by day 4, with discharge on day 5. No reoperations were required, and pain control was effective, with the visual analog scale (VAS) score reducing from a maximum of 3 on the day of surgery. Laparoscopic gastrojejunostomy is a safe and effective approach for treating gastric outlet obstruction, providing favourable outcomes in both benign and malignant cases. The procedure is associated with low morbidity, minimal postoperative complications, and effective symptom relief, making it an optimal surgical option which is arguably superior to open gastrojejunostomy for managing GOO.